Implementation of Islamic Religious Education for 10th Grade Students at SMA Ar Rahman Medan - Putri, Nisya Aulia Armaya; Lubis, Sakban (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
This study aims to examine the implementation of Islamic Religious Education (IRE) for 10th-grade students at SMA Ar Rahman Medan. The research employs a qualitative method with data collection techniques that include interviews, observations, and documentation. The findings indicate that the implementation of IRE at SMA Ar Rahman Medan has been carried out effectively, particularly in religious activities such as congregational prayers and religious study sessions. However, challenges such as varying levels of students' religious understanding and limited instructional time pose obstacles to the effective delivery of IRE. Additionally, the supportive religious environment of the school and the role of teachers as role models and moral guides have positively impacted the development of students' religious character. This study is expected to provide recommendations for improving teaching methods and IRE strategies to be more effective in achieving character education goals.